Método de sincronização aplicado a conversores PWM trifásicos - Camargo, Robinson Figueiredo de (2006)
In the last decade, disturbances in the electrical system have been increased, mainly due to proliferation of nonlinear loads. As a result harmonic distortion, voltage unbalance and frequency variations are becoming a concern. These disturbances can produce distortions in the synchronization signals used by PWM converters connected to utility grid. Theses distortions in the synchronization signals, consequently, increase distortions in generated or drained currents by the three-phase PWM converters. Due these facts, several synchronization methods are developed with purpose to operate adequately to reduce the impacts of corrupting grid voltages on the synchronization signals. In this sense, synchronization methods that used closed loop and open loop algorithms are proposed in the literature. Although closed loop methods have low sensitivity to the frequency variations, a trade of between good transient response and good filtering characteristics must always be considered. Moreover, the algorithms developed to the closed loop methods on fixed point DSP, generally, present larger execution time those open loop synchronization methods.Open loop methods standout for their simplicity as compare closed loop methods. However, none of open loop methods reported, so far, have a good performance in terms of the distortion synchronization signals and consequently in the generated or drained currents in the three-phase PWM converters under unbalance, harmonics and frequency variations in the grid voltages. In this sense, this Doctor Thesis proposes a study, analysis and development of a new open loop synchronization method applied on three-phase three-wire and four-wire PWM converters connected to the utility grid. This method provides a good performance even in the presence of harmonics, severe voltage unbalance and frequency variations on grid voltages. Initially, it is presented an overview of open loop synchronization method applied to three-phase PWM converters. Then, have been situated the characteristics and limitations of the new method under grid voltages disturbances. In addition, the proposed method is implemented considering that two distinct cases. The first case describes the implementation of the new synchronization method to synchronized three-phase three-wire PWM rectifiers. The second case presents the implementation of the new synchronization method to generate reference currents to three-phase four-wire shunt active power filter. Furthermore, simulation and experimental results are obtained to demonstrate the good performance of the new open-loop synchronization method used in three-phase threewire and four-wire PWM converters along the Thesis.